Novel Missense Variants in ADAT3 as a Cause of Syndromic Intellectual Disability - Thomas, Elizabeth; Lewis, Andrea M.; Yang, Yaping; Chanprasert, Sirisak; Potocki, Lorraine; Scott, Daryl A. (Journal of Pediatric Genetics, 2019)
Autosomal recessive variants in the adenosine deaminase, tRNA specific 3 (ADAT3) gene cause a syndromic form of intellectual disability due to a loss of ADAT3 function. This disorder is characterized by developmental delay, intellectual disability, speech delay, abnormal brain structure, strabismus, microcephaly, and failure to thrive. A small subset of individuals with ADAT3 deficiency have other structural birth defects including atrial septal defect, patent ductus arteriosus, hypospadias, cryptorchidism, and micropenis. Here, we report a sibling pair with novel compound heterozygous missense variants that affect a conserved amino acid in the deaminase domain of ADAT3. These siblings have many of the features characteristic of this syndrome, including, intellectual disability, hypotonia, esotropia, failure to thrive, and microcephaly. Both had gastroesophageal reflux disease (GERD), feeding problems, and aspiration requiring thickening of feeds. Although they have no words, their communication abilities progressed rapidly when they began to use augmentative and alternative communication (AAC) devices. One of these siblings was born with an anterior congenital diaphragmatic hernia, which has not been reported previously in association with ADAT3 deficiency. We conclude that individuals with ADAT3 deficiency should be monitored for GERD, feeding problems, and aspiration in infancy. They may also benefit from the use of AAC devices and individualized educational programs that take into account their capacity for nonverbal language development. Additional studies in humans or animal models will be needed to determine if ADAT3 deficiency predisposes to the development of structural birth defects.
Keywords: ADAT3; mental retardation autosomal recessive 36; syndromic intellectual disability; congenital diaphragmatic hernia; augmentative and alternative communication devices